Seleksi Parameter yang Mempengaruhi Sintesis Kalkon dengan Metode Plackett-Burman - Indah Silvia Sugiyamin; Harra Ismi Farah; Agung Rahmadani; Angga Cipta Narsa (Proceeding of Mulawarman Pharmaceuticals Conferences, 2020)
Chalcone is a compound that has various biological activities. The organic synthesis approach has been widely used to obtain chalcone compouds. The aim of this research is to select the main parameters which influence chalcone synthesis. This study was conducted using Plackett-Burman experimental design. Of eleven parameters used, eight of them showed a significant effect on the yield of chalcones namely temperature, reaction time, mole number of benzaldehyde, volume of acetophenone solvent, incubation time, volume of distilled water, volume of benzaldehyde solvent, catalyst volume and dummy. In addition, the highest yield is 32.43%.